2.5.4 higher order ode exact

Table 2.509: higher order ode exact

#

ODE

CAS classification

Solved?

1466

\[ {}x y^{\prime \prime \prime }-y^{\prime \prime } = 0 \]

[[_3rd_order, _missing_y]]

3499

\[ {}x y^{\prime \prime \prime }+2 y^{\prime \prime } = A x \]

[[_3rd_order, _missing_y]]

6913

\[ {}x^{2} y^{\prime \prime \prime }-3 x y^{\prime \prime }+3 y^{\prime } = 0 \]

[[_3rd_order, _missing_y]]

8038

\[ {}x^{3} y^{\prime \prime \prime \prime }+8 x^{2} y^{\prime \prime \prime }+8 x y^{\prime \prime }-8 y^{\prime } = 0 \]

[[_high_order, _missing_y]]

8572

\[ {}y^{\prime \prime \prime }+x^{2} y^{\prime \prime }+5 y^{\prime } x +3 y = 0 \]

[[_3rd_order, _exact, _linear, _homogeneous]]

11473

\[ {}y^{\prime \prime \prime }-y^{\prime \prime } \sin \left (x \right )-2 y^{\prime } \cos \left (x \right )+y \sin \left (x \right )-\ln \left (x \right ) = 0 \]

[[_3rd_order, _fully, _exact, _linear]]

11484

\[ {}x y^{\prime \prime \prime }+\left (x^{2}-3\right ) y^{\prime \prime }+4 y^{\prime } x +2 y-f \left (x \right ) = 0 \]

[[_3rd_order, _fully, _exact, _linear]]

11488

\[ {}\left (x -2\right ) x y^{\prime \prime \prime }-\left (x -2\right ) x y^{\prime \prime }-2 y^{\prime }+2 y = 0 \]

[[_3rd_order, _exact, _linear, _homogeneous]]

11490

\[ {}\left (2 x -1\right ) y^{\prime \prime \prime }+\left (x +4\right ) y^{\prime \prime }+2 y^{\prime } = 0 \]

[[_3rd_order, _missing_y]]

11497

\[ {}x^{2} y^{\prime \prime \prime }+5 x y^{\prime \prime }+4 y^{\prime }-\ln \left (x \right ) = 0 \]

[[_3rd_order, _missing_y]]

11498

\[ {}x^{2} y^{\prime \prime \prime }+6 x y^{\prime \prime }+6 y^{\prime } = 0 \]

[[_3rd_order, _missing_y]]

11506

\[ {}\left (x^{2}+1\right ) y^{\prime \prime \prime }+8 x y^{\prime \prime }+10 y^{\prime }-3+\frac {1}{x^{2}}-2 \ln \left (x \right ) = 0 \]

[[_3rd_order, _missing_y]]

11529

\[ {}y^{\prime \prime \prime } \sin \left (x \right )+\left (2 \cos \left (x \right )+1\right ) y^{\prime \prime }-y^{\prime } \sin \left (x \right )-\cos \left (x \right ) = 0 \]

[[_3rd_order, _missing_y]]

11530

\[ {}\left (\sin \left (x \right )+x \right ) y^{\prime \prime \prime }+3 \left (\cos \left (x \right )+1\right ) y^{\prime \prime }-3 y^{\prime } \sin \left (x \right )-y \cos \left (x \right )+\sin \left (x \right ) = 0 \]

[[_3rd_order, _fully, _exact, _linear]]

11548

\[ {}x y^{\prime \prime \prime \prime }+5 y^{\prime \prime \prime }-24 = 0 \]

[[_high_order, _missing_y]]

11552

\[ {}x^{2} y^{\prime \prime \prime \prime }+4 x y^{\prime \prime \prime }+2 y^{\prime \prime } = 0 \]

[[_high_order, _missing_y]]

11553

\[ {}x^{2} y^{\prime \prime \prime \prime }+6 x y^{\prime \prime \prime }+6 y^{\prime \prime } = 0 \]

[[_high_order, _missing_y]]

11555

\[ {}x^{2} y^{\prime \prime \prime \prime }+8 x y^{\prime \prime \prime }+12 y^{\prime \prime } = 0 \]

[[_high_order, _missing_y]]

11559

\[ {}x^{3} y^{\prime \prime \prime \prime }+6 x^{2} y^{\prime \prime \prime }+6 x y^{\prime \prime } = 0 \]

[[_high_order, _missing_y]]

11572

\[ {}\left ({\mathrm e}^{x}+2 x \right ) y^{\prime \prime \prime \prime }+4 \left ({\mathrm e}^{x}+2\right ) y^{\prime \prime \prime }+6 \,{\mathrm e}^{x} y^{\prime \prime }+4 \,{\mathrm e}^{x} y^{\prime }+y \,{\mathrm e}^{x}-\frac {1}{x^{5}} = 0 \]

[[_high_order, _fully, _exact, _linear]]

12999

\[ {}\left (x +2\right )^{2} y^{\prime \prime \prime }+\left (x +2\right ) y^{\prime \prime }+y^{\prime } = 1 \]

[[_3rd_order, _missing_y]]

13002

\[ {}\left (x^{3}-x \right ) y^{\prime \prime \prime }+\left (8 x^{2}-3\right ) y^{\prime \prime }+14 y^{\prime } x +4 y = 0 \]

[[_3rd_order, _fully, _exact, _linear]]

13015

\[ {}\left (x^{3}+1\right ) y^{\prime \prime \prime }+9 x^{2} y^{\prime \prime }+18 y^{\prime } x +6 y = 0 \]

[[_3rd_order, _fully, _exact, _linear]]

13022

\[ {}4 x^{2} y^{\prime \prime \prime }+8 x y^{\prime \prime }+y^{\prime } = 0 \]

[[_3rd_order, _missing_y]]

14227

\[ {}x y^{\prime \prime \prime } = 2 \]

[[_3rd_order, _quadrature]]

15225

\[ {}x y^{\prime \prime \prime }+2 y^{\prime \prime } = 6 x \]

[[_3rd_order, _missing_y]]

15248

\[ {}x y^{\prime \prime \prime }+2 y^{\prime \prime } = 6 x \]
i.c.

[[_3rd_order, _missing_y]]

16439

\[ {}t y^{\prime \prime \prime \prime }+2 y^{\prime \prime \prime } = \frac {45}{8 t^{{7}/{2}}} \]
i.c.

[[_high_order, _missing_y]]

16459

\[ {}x^{3} y^{\prime \prime \prime \prime }+6 x^{2} y^{\prime \prime \prime }+7 x y^{\prime \prime }+y^{\prime } = 0 \]

[[_high_order, _missing_y]]

16907

\[ {}x y^{\prime \prime \prime } = 2 \]

[[_3rd_order, _quadrature]]

16928

\[ {}x y^{\prime \prime \prime }-y^{\prime \prime } = 0 \]

[[_3rd_order, _missing_y]]

17123

\[ {}x^{2} y^{\prime \prime \prime }-3 x y^{\prime \prime }+3 y^{\prime } = 0 \]

[[_3rd_order, _missing_y]]

17124

\[ {}x^{2} y^{\prime \prime \prime } = 2 y^{\prime } \]

[[_3rd_order, _missing_y]]

17125

\[ {}\left (x +1\right )^{2} y^{\prime \prime \prime }-12 y^{\prime } = 0 \]

[[_3rd_order, _missing_y]]

17126

\[ {}\left (2 x +1\right )^{2} y^{\prime \prime \prime }+2 \left (2 x +1\right ) y^{\prime \prime }+y^{\prime } = 0 \]

[[_3rd_order, _missing_y]]

17196

\[ {}x^{2} y^{\prime \prime \prime \prime }+4 x y^{\prime \prime \prime }+2 y^{\prime \prime } = 0 \]
i.c.

[[_high_order, _missing_y]]

17197

\[ {}x^{3} y^{\prime \prime \prime \prime }+6 x^{2} y^{\prime \prime \prime }+6 x y^{\prime \prime } = 0 \]
i.c.

[[_high_order, _missing_y]]

17812

\[ {}x y^{\prime \prime \prime }-y^{\prime \prime } = 0 \]

[[_3rd_order, _missing_y]]

18000

\[ {}\left (-x^{2}+1\right ) y^{\prime \prime \prime }-x y^{\prime \prime }+y^{\prime } = 0 \]

[[_3rd_order, _missing_y]]

18379

\[ {}x^{3} y^{\prime \prime \prime \prime }+8 x^{2} y^{\prime \prime \prime }+8 x y^{\prime \prime }-8 y^{\prime } = 0 \]

[[_high_order, _missing_y]]

18696

\[ {}\left (x^{3}+x^{2}-3 x +1\right ) y^{\prime \prime \prime }+\left (9 x^{2}+6 x -9\right ) y^{\prime \prime }+\left (18 x +6\right ) y^{\prime }+6 y = x^{3} \]

[[_3rd_order, _fully, _exact, _linear]]

18697

\[ {}x^{2} y^{\prime \prime \prime }+5 x y^{\prime \prime }+4 y^{\prime } = -\frac {1}{x^{2}} \]

[[_3rd_order, _missing_y]]

18947

\[ {}x y^{\prime \prime \prime }+\left (x^{2}-3\right ) y^{\prime \prime }+4 y^{\prime } x +2 y = 0 \]

[[_3rd_order, _fully, _exact, _linear]]

18955

\[ {}x^{2} y^{\prime \prime \prime \prime }+1 = 0 \]

[[_high_order, _quadrature]]

18961

\[ {}x^{2} y^{\prime \prime \prime }-4 x y^{\prime \prime }+6 y^{\prime } = 4 \]

[[_3rd_order, _missing_y]]

18971

\[ {}x^{2} y^{\prime \prime \prime \prime }+a^{2} y^{\prime \prime } = 0 \]

[[_high_order, _missing_y]]

18985

\[ {}x^{3} y^{\prime \prime \prime }+4 x^{2} y^{\prime \prime }+x \left (x^{2}+2\right ) y^{\prime }+3 x^{2} y = 2 x \]

[[_3rd_order, _exact, _linear, _nonhomogeneous]]

18988

\[ {}\left (x^{3}-x \right ) y^{\prime \prime \prime }+\left (8 x^{2}-3\right ) y^{\prime \prime }+14 y^{\prime } x +4 y = \frac {2}{x^{3}} \]

[[_3rd_order, _fully, _exact, _linear]]

18992

\[ {}x y^{\prime \prime \prime }-x y^{\prime \prime }-y^{\prime } = 0 \]

[[_3rd_order, _missing_y]]

18997

\[ {}y^{\prime \prime \prime }+\cos \left (x \right ) y^{\prime \prime }-2 y^{\prime } \sin \left (x \right )-y \cos \left (x \right ) = \sin \left (2 x \right ) \]

[[_3rd_order, _fully, _exact, _linear]]

19318

\[ {}x^{2} y^{\prime \prime \prime }-2 y^{\prime } = 0 \]

[[_3rd_order, _missing_y]]

19321

\[ {}x^{2} y^{\prime \prime \prime }+x y^{\prime \prime }-4 y^{\prime } = 0 \]

[[_3rd_order, _missing_y]]

19324

\[ {}x^{2} y^{\prime \prime \prime }+3 x y^{\prime \prime }+2 y^{\prime } = 0 \]

[[_3rd_order, _missing_y]]

19335

\[ {}x^{2} y^{\prime \prime \prime }+3 x y^{\prime \prime }+2 y^{\prime } = x \]

[[_3rd_order, _missing_y]]

19351

\[ {}x y^{\prime \prime \prime }+\left (x^{2}-3\right ) y^{\prime \prime }+4 y^{\prime } x +2 y = 0 \]

[[_3rd_order, _fully, _exact, _linear]]

19362

\[ {}x^{3} y^{\prime \prime \prime }+4 x^{2} y^{\prime \prime }+x \left (x^{2}+2\right ) y^{\prime }+3 x^{2} y = 2 x \]

[[_3rd_order, _exact, _linear, _nonhomogeneous]]

19384

\[ {}x^{2} y^{\prime \prime \prime }-4 x y^{\prime \prime }+6 y^{\prime } = 4 \]

[[_3rd_order, _missing_y]]

19389

\[ {}x y^{\prime \prime \prime }-x y^{\prime \prime }-y^{\prime } = 0 \]

[[_3rd_order, _missing_y]]

19412

\[ {}x^{2} y^{\prime \prime \prime \prime }+a^{2} y^{\prime \prime } = 0 \]

[[_high_order, _missing_y]]

19413

\[ {}x^{2} y^{\prime \prime \prime \prime } = \lambda y^{\prime \prime } \]

[[_high_order, _missing_y]]

19424

\[ {}x^{2} y^{\prime \prime \prime \prime }+1 = 0 \]

[[_high_order, _quadrature]]

19434

\[ {}\left (x^{3}-4 x \right ) y^{\prime \prime \prime }+\left (9 x^{2}-4\right ) y^{\prime \prime }+18 y^{\prime } x +6 y = 6 \]

[[_3rd_order, _fully, _exact, _linear]]

19593

\[ {}\left (x^{2}+x +1\right ) y^{\prime \prime \prime }+\left (3+6 x \right ) y^{\prime \prime }+6 y^{\prime } = 0 \]

[[_3rd_order, _missing_y]]

19594

\[ {}\left (x^{3}-x \right ) y^{\prime \prime \prime }+\left (8 x^{2}-3\right ) y^{\prime \prime }+14 y^{\prime } x +4 y = \frac {2}{x^{3}} \]

[[_3rd_order, _fully, _exact, _linear]]

19595

\[ {}y^{\prime \prime \prime }+\cos \left (x \right ) y^{\prime \prime }-2 y^{\prime } \sin \left (x \right )-y \cos \left (x \right ) = \sin \left (2 x \right ) \]

[[_3rd_order, _fully, _exact, _linear]]